Biometric and reproductive aspects of Boquichico Prochilodus nigricans Agassiz, 1829 (Pisces: Prochilodontidae) in Ucayali, Perú - Riofrío Q., José C. (2002)
The knowledge of biology and fishery is essential for an adequate management and a sustained production. Boquichico (Prochilodus nigricans) is one of the principal components of the fish catch in Ucayali. From February to December, 1994, the sex proportion, reproduction season, mature length and Total length/Weight ratios (LT-PT) of boquichico were recorded and analyzed. The LT-PT between males and females, suggests the use of a unique PT = 0,0211 LT 2.8592 model for both sexes. Sexual proportion was essentially 1:1 by the χ 2 0,05 criterion. Maturity stages progression analyses confirm that the reproduction of boquichico occurs during the Ucayali river flood (October-January). Calculated mature length were 24,5 cm and 26,1 cm for males and females, respectively.